Boosting MSMEs: how digital financial innovation and financial literacy fuel access to finances - Putra, Komang Widhya Sedana; Lasmi, Ni Wayan (LPPM ISNJ Bengkalis, 2025)
Purpose – This study explores how digital financial innovation and literacy collectively promote access to finance and MSMEs growth in Bali, Indonesia. Intends to ascertain how these two factors combine to enhance access to finance and, subsequently, MSME growth. Method – Data collection was carried out through questionnaires using a quantitative approach. The study targeted the owners of MSMEs in Bali, using purposive sampling to select 200 respondents who have actively utilized digital financial services. The data were analyzed using structural equation modeling (SEM) to quantify the associations among key variables. Findings – The results show that financial literacy is an important mediator in ensuring digital financial innovation translates into access to finance and, subsequently, MSME growth. This, therefore, offers strong proof that a boost in financial literacy among MSME owners in developing countries will further sweeten the benefits of digital financial innovations into better chances of securing finance for business expansion. The research explores how financial literacy and digital financial innovation expand access to finance and MSME development in Bali, using disruptive innovation theory, theory of access to finance, theory of financial literacy, and TAM. Evidence confirms financial literacy as an essential mediator, increasing the impact of digital finance. Implications – Theoretically, this integrates multiple frameworks; practically, it demands increased financial literacy awareness to harness digital innovation value to MSME development and inclusion fully.